Pre-treatment tumour perfusion parameters and initial RECIST response do not predict long-term survival outcomes for patients with head and neck squamous cell carcinoma treated with induction chemotherapy. - Natalie M Lowe; Lucy E Kershaw; Jonathan M Bernstein; Stephanie B Withey; Kathleen Mais; Jarrod J Homer; Nicholas J Slevin; Suzanne C Bonington; Bernadette M Carrington; Catharine M West (PLoS ONE, 2018)
Previously, we showed that pre-treatment tumour plasma perfusion (Fp) predicts RECIST response to induction chemotherapy (ICT) in locoregionally advanced head and neck squamous cell carcinoma (HNSCC). The aim here was to determine whether the pre-treatment tumour Fp estimate, changes in tumour Fp or RECIST response post 2 cycles of ICT were prognostic for long-term survival outcomes.A prospective study enrolled patients with high stage HNSCC treated with docetaxel (T), cisplatin (P) and 5-fluorouracil (F) (ICT) followed by synchronous cisplatin and intensity modulated radiotherapy. Dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) before and after two cycles of ICT was used to measure Fp and RECIST response.Forty-two patients were recruited and 37 underwent two scans. The median follow-up was 36 (range 23-49) months. Pre-treatment tumour Fp (stratified by median) was not prognostic for overall survival (p = 0.42), disease specific survival (p = 0.20) and locoregional control (p = 0.64). Neither change in tumour Fp nor RECIST response post two cycles of ICT was prognostic for any outcome (p>0.21).DCE-MRI parameters do not predict long-term survival outcomes following ICT and RECIST response to ICT may not be an appropriate endpoint to determine early efficacy of a treatment in HNSCC patients.